FORECASTING THE MARKET NEED FOR CEMENT FROM 2014 - 2045 TO SUPPORT THE FEASIBILITY OF ESTABLISHING CEMENT FACTORIES IN IRAQ - Assist. Prof. Dr. Ali Abdulhussein Khaleel Alfadhel (MBA); Assistant Professor Dr. Ali Mahmood Ali Samaka; Maytham Jabaar Farhan Abedi. (MFB) (Journal Park Publishing, 2023)
The current research aims to identify the capability of the Iraqi economy to establish or rehabilitate cement factories to meet market needs, in addition to competing with external competitors in terms of quality, cost, and production methods. The research problem is represented by the inability of the Iraqi economy to establish new factories or rehabilitate the old ones to meet the needs of the internal sectors as well as the internal and external markets. Furthermore, population growth is increasing, and urban development is going on. The research sample was chosen by applying a study to the Iraqi Cement State Company (a government company) and cement investment companies (private sector) in the Iraqi economy. The current research has adopted two complementary methods: The first one is the descriptive method, which refers to the theoretical side of the study, and the second one includes the analytical and measurement aspects. The research hypotheses were analyzed and tested statistically through the use of statistical programs and standards (Excel and SPSS) to reach the desired goal of this research.
Keywords: feasibility studies, cement industry.